Development of Audio Visual Media to Introduce Shapes and Colors in English to Children Aged 5-6 Years in Kindergarten Kasih Bapa Percut T.A 2023/2024 - Silaban, Lina Br.; Eza, Gita Noveri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research focuses on analyzing the validity of developing learning media. This research is R&D (Research and Development) research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research was carried out to determine the feasibility and practicality of technology-based Audio Visual learning media. The subjects of this research were two lecturers as material experts and media experts, 15 TK B group students, and a TK B class teacher as a practitioner. Based on the research results, a score of 82 was obtained from material experts with a feasibility percentage of 96.4% in the